A farmacopuntura com xilazina para sedação em cães - Faria, Artur Bento de (2007)
Previous studies with pharmacopuncture in dogs showed its advantage for sedation, minimizing undesirable effects. The use of pharmocopuncture with xylazine in Yin Tang acupoint of dogs is investigated. Eight dogs were randomly submitted to four different treatment protocols according to a Latin Square double blind design: 1) 0.01 mL/kg of saline injected into Yin Tang acupoint (aquapuncture), 2) 1 mg/kg of xylazine injected subcutaneously at the dorsal region, 3) 0.2 mg/kg of xylazine injected subcutaneously at the dorsal region and 4) 0.2 mg/kg of xylazine injected into Yin-Tang acupoint (pharmacopuncture). Rectal temperature, heart and respiratory rates, arterial blood pressure, oxygen hemoglobin saturation and pulse rate and degree of sedation were measured before and at 5, 10, 30, 40, 50 and 60 minutes after treatments. Sedation was observed in xylazine and pharmacopuncture groups while saline injection and sub -dose of xylazine did not induce sedation. Both xylazine and pharmacopuncture induced reduction in respiratory rate, heart rate and arterial blood pressure. In conclusion, pharmacopuncture and the conventional dose of xylazine produced similar sedation in dogs. The results indicate the potential application of pharmacopuncture in dogs. Further studies could elucidate the optimal doses, drugs and acupoints to achieve the best effect.